Regional homogeneity alterations in multifrequency bands in patients with basal ganglia stroke: A resting-state functional magnetic resonance imaging study - Li, Qianqian; Hu, Su; Mo, Yingmin; Chen, Hao; Meng, Chaoguo; Zhan, Linlin; Li, Mengting; Quan, Xuemei; Gao, Yanyan; Cheng, Lulu; Hao, Zeqi; Jia, Xize; et al. (Frontiers in Aging Neuroscience, 2022)
Objective: To investigate the spontaneous regional neural activity abnormalities in patients with acute basal ganglia ischemic stroke (BGIS) using a multi-frequency bands regional homogeneity (ReHo) method and to explore whether the alteration of ReHo values were associated with clinical characteristics. Method: In this study, thirty-four acute BGIS patients and forty-four healthy controls (HCs) were recruited. All participants were examined by resting-state functional magnetic resonance imaging (rs-fMRI). ReHo method was used to detect the alterations of spontaneous neural activities in acute BGIS patients. A two sample t-test comparison was performed to compare the ReHo value between the two groups, and a Pearson correlation analysis was conducted to assess the relationship between the regional neural activity abnormalities and clinic characteristics. Results: Compared with the HCs, the acute BGIS patients showed increased ReHo in left caudate, and sub-region such as right caudate and left putamen in conventional frequency bands. In slow-5 frequency band, BGIS patients showed decreased ReHo in left medial cingulum of BGIS compared to the HCs and other sub-regions such as bilateral caudate and left putamen. No brain regions with ReHo alterations were found in the slow-4 frequency band. Moreover, we found the ReHo value of left caudate was positively correlated with the NIHSS score. Conclusion: Our findings revealed the alterations of ReHo in acute BGIS patients in specific frequency band and provided a new insight for pathogenesis mechanism of BGIS. The present study demonstrated the frequency-specific characteristics of ReHo in acute BGIS patients which may have positive effect on the future neuroimaging studies.